Modulating Cell‐Surface Receptor Signaling and Ion Channel Functions by In Situ Glycan Editing. (2nd January 2018) - Jiang, Hao; López‐Aguilar, Aimé; Meng, Lu; Gao, Zhongwei; Liu, Yani; Tian, Xiao; Yu, Guangli; Ovryn, Ben; Moremen, Kelley W.; Wu, Peng
Abstract: Glycans anchored on cell‐surface receptors are active modulators of receptor signaling. A strategy is presented that enforces transient changes to cell‐surface glycosylation patterns to tune receptor signaling. This approach, termed in situ glycan editing, exploits recombinant glycosyltransferases to incorporate monosaccharides with linkage specificity onto receptors in situ. α2, 3‐linked sialic acid or α1, 3‐linked fucose added in situ suppresses signaling through epidermal growth factor receptor and fibroblast growth factor receptor. We also applied the same strategy to regulate the electrical signaling of a potassium ion channel–human ether‐à‐go‐go‐related gene channel. Compared to gene editing, no long‐term perturbations are introduced to the treated cells. In situ glycan editing therefore offers a promising approach for studying the dynamic role of specific glycans in membrane receptor signaling and ion channel functions.